External ear canal cholesteatoma after ventilation tube insertion and mastoidectomy - Đerić Dragoslava; Jovanović Milan B.; Baljošević Ivan; Blažić Srbislav; Milojević Milanko (Vojnosanitetski Pregled)
Introduction. Etiopathogenetically, there are two types of chollesteatomas: congenital, and acquired. Numerous theories in the literature try to explain the nature of the disease, however, the question about cholesteatomas remain still unanswered. The aim of the study was to present a case of external ear canal cholesteatoma (EEC) developed following microsurgery (ventilation tube insertion and mastoidectomy), as well as to point ant possible mechanisms if its development. Case report. A 16-yearold boy presented a 4-month sense of fullness in the ear and otalgia on the left side. A year before, mastoidectomy and posterior atticotomy were performed with ventilation tube placement due to acute purulent mastoiditis. Diagnosis was based on otoscopy examination, audiology and computed tomography (CT) findings. CT showed an obliterative soft-tissue mass completely filled the external ear canal with associated erosion of subjacent the bone. There were squamous epithelial links between the canal cholesteatoma and lateral tympanic membrane surface. They originated from the margins of tympanic membrane incision made for a ventilation tube (VT) insertion. The position of VT was good as well as the aeration of the middle ear cavity. The tympanic membrane was intact and of normal appearance without middle ear extension or mastoid involvement of cholesteatoma. Cholesteatoma and ventilation tube were both removed. The patient recovered without complications and shortly audiology revealed hearing improving. Follow-up 2 years later, however, showed no signs of the disease. Conclusion. There could be more than one potential delicate mechanism of developing EEC in the ear with VT insertion and mastoidectomy. It is necessary to perform routine otologic surveillance in all patients with tubes. Affected ear CT scan is very helpful in showing the extent of cholesteatoma and bony defects, which could not be assessed by otoscopic examination alone.